Desenho institucional, poliarquia decisória e formulação da política de mudanças climáticas no Brasil: estudo de caso da comissão interministerial de mudança global do clima - Rodrigues, Diego de Freitas (2013)
It has been observed that the same governance model was configurated in the brazilian climate change policy, characterizing by this policy to the responsible institutions three factors in comon: (1) institutional diversity, (2) cooperation e (3) political competition. Trough a Case Study, it was attempted to focus, as an unity of analisys, on the Interministerial Comission on Global Climate Change (CIMMGC in portuguese) to observe in what measure the bigger institutional diversity, characterized by the elevated inclusiveness of political actors and the accountability reinforcement in the political decision making process, promoted more cooperation and less political competition among the political actors involved in CIMMGC. In this scenery, the research question was: In the contexto of a diverse institutional composition and of it s political decision making process rules (supported by the unanimity rule), why, by observing the political decision making processo f the CIMMGC, wasn t possible to point a decision making paralisys or an institutional immobility in it s acitivities? The Hypothesis was that the institutional drawing of the CIMMGC worked as a political vector of dynamism through the decision making rules developed during the institutionalization of brazilian climate change policy. Were applied in this study, specially, two integrated data collection strategies: (1) query and analisys of institutional reports issued specially by the CIMMGC, but also issued by other institutional organisms vinculated to the governance of brazilian climate change policy and (2) interviews in depth and semi-structured with policy makers directly involved with national climate change policy and specially allocated in the CIMMGC. The results pointed that a bigger political inclusiveness in the decision making process of the brazilian climate change policy incurred in no absence of democratic governance. In the case of the CIMMGC, the brazilian climate change policy consensual model reinforced the accountability mechanisms in the political process without losing the institutional dynamism and the decision making capability in the political goals granted to the institution by the Climate Change National Policy and Plan.